Nasîruddin et-Tûsî ve Musikî Risalesi - Fazlı Arslan (Dini Araştırmalar, 2015)
Nasîr al-Dîn al-Tûsî was a noted astronomer and mathematician. His writings dealt with both religious topics and non-religious subjects. His popular fame is based upon a large number of treatises. His works all are well-known except "Risâla fi İlm al-Mûsîkâ" which was written about theory of music. Risâla were discussed in this study and translated into Turkish. Risâla includes many  musical terms as intervalic ratios, establishment of intervals and their proportions, and names, consonances-disconances, and rhytmic analysis